Anuran species in Brazil's protected areas network - Morais, Alessandro Ribeiro; Andreani, Tainã Lucas; Alves, Rhayane; Dos Santos, Carolina Emília; Barros, Jhonatan; Rezende, Wadson Rodrigues [UNESP]; Lemes, Priscila (British Herpetological Society, 2020)
Amphibians are one of the most threatened among the vertebrates species and urgently require conservation protection and planning. The establishment of protected areas (PAs) is one of the most important strategies in protecting biodiversity, as they offer a partial solution to habitat modification. Our main objective was to analyse the temporal and spatial trends in the anuran species inventories of PAs in Brazil, therefore providing an extensive list of anuran species in the Brazilian PAs network for the first time. We considered a combination of keywords while using the data on “Scopus”, “Scielo”, and “Web of Science”. We found 115 papers that published anuran species lists for 101 Brazilian protected areas. Overall, we registered 605 species distributed in 20 families. Only seven out of the 605 anuran species registered in the present study are threatened by extinction and 40 are listed as Data Deficient. The number of anuran species inventories in Brazilian protected areas has increased over time (r = 0.17; r2 = 0.267; p<0.01), with its peak in 2011 (n = 15 inventories). The majority of the species inventories were conducted in protected areas located in the Atlantic Forest (55.45 %). The number of anuran species per protected area varied from seven to 80; however, we did not find any relationship between the species richness and size of the protected areas (r2 = 0.027; r = 0.165; p = 0.092). Our results can be useful to fill the gaps and integrate knowledge; and this reinforces the importance of the present study in contributing to the knowledge and conservation of anuran species in Brazil.
Keywords: Brazilian biomes; Inventory; Species list; Temporal and spatial trends